2012
DOI: 10.1155/2012/450491
|View full text |Cite
|
Sign up to set email alerts
|

Mixing Study in an Unbaffled Stirred Precipitator Using LES Modelling

Abstract: This paper describes the CFD modelling of a reactor operating in the nuclear industry using LES approach. The reactor consists of an unbaffled stirred tank reactor in which plutonium precipitation reactions are carried out. The flow generated in such a precipitator is complex and there is very little information available in the literature about unbaffled reactors stirred with magnetic rod. That is why a hydrodynamic modelling has been developed using computational fluid dynamics (CFD) in order to get accurate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…CFD-PBM coupled mechanistic models have been developed to predict the effect of process parameters on product crystal properties in pharmaceutical [152], minerals [153], and nuclear industry [154,155]. Review by Bałdyga elaborates application of CFD-PBM models to 'design' product particles [152].…”
Section: Crystallization and Precipitation In Stirred Tankmentioning
confidence: 99%
See 1 more Smart Citation
“…CFD-PBM coupled mechanistic models have been developed to predict the effect of process parameters on product crystal properties in pharmaceutical [152], minerals [153], and nuclear industry [154,155]. Review by Bałdyga elaborates application of CFD-PBM models to 'design' product particles [152].…”
Section: Crystallization and Precipitation In Stirred Tankmentioning
confidence: 99%
“…The model can be further used for scale-up investigations including how the mean size, size distribution, nucleation rate changes with scale up (specific power input, tank volume). The CFD-PBM models have been used to predict size evolution of uranium oxalate crystals during precipitation reaction in the nuclear industry [154,155]. Simulation of the flow field allowed accurate description of mixing and effect of hydrodynamics on the precipitate properties.…”
Section: Crystallization and Precipitation In Stirred Tankmentioning
confidence: 99%
“…Bertrand et al studied the plutonium precipitation reaction in a vortexing unbaffled stirred tank reactor. [ 20 ] In their experimental results, it was observed that the mean size of crystal size distribution varied significantly depending on the injection position of reagents. When injected into the free vortex, the reagents mixed uniformly and enhanced the crystal growth process, resulting in larger crystals.…”
Section: Introductionmentioning
confidence: 99%